O pós-operatório de cirurgia cardíaca na percepção de pacientes - Gois, Cristiane Franca Lisboa (2005)
This study aimed to know the patients' perception regarding the experience of undergoing cardiac surgery and staying in an Intensive Care Unit (ICU) and to identify the factors that generate stress for patients during their stay in the ICU. This is a qualitative research of a descriptive and exploratory character, carried out with eight patients who underwent cardiac surgery and admitted to the specialized unit, which is part of a public hospital, a reference in the interior of the State of São Paulo. Data were collected through interviews and a questionnaire to characterize patients' socio-demographic and clinical data. The analysis of the interviews was carried out using content analysis, in the thematic analysis mode. The following themes emerged in this study: the ICU environment and the postoperative period: remarkable experience; unpleasant experience: thirst, tube, and pain, relationships with health professionals: impersonality, professional presence meaning security and, guidance and information meaning security and clarification; after the surgical experience: fear and anxiety as something already overcome.